Bread-making synthesis of hierarchically Co@C nanoarchitecture in heteroatom doped porous carbons for oxidative degradation of emerging contaminants - Tian, W.; Zhang, H.; Qian, Z.; Ouyang, T.; Sun, H.; Qin, J.; Tade, Moses; Wang, Shaobin (Elsevier BV, 2018)
Employing low-cost and abundant wheat flour, sodium bicarbonate, cysteine and cobalt nitrate as precursors, we for the first time present a facile one-pot pyrolysis strategy for homogeneous assembly of core-shell Co@C nanoparticles with nitrogen and sulfur into hierarchically porous carbons (Co-N-S-PCs). The samples are highly efficient for oxidative decomposition of p-hydroxybenzoic acid (HBA) and phenol. It was found that Co@C nanoparticles are crucial for the generation of singlet oxygen in advanced oxidation processes (AOPs), which works together with hydroxyl and sulfate radicals in efficient decomposition of HBA. Density functional theory (DFT) calculations disclose that electron transfer from metal Co to C shells greatly improves the Fermi level and chemical activity of the C atoms. The combination of Co-C interaction with N, S codoping further bring in catalytic active sites in the graphitic shells where the charge states of C atoms are increased. This template-free strategy is scalable to prepare highly efficient catalysts, including functional carbon materials modified with non-precious metal species or pure and well-dispersed porous core-shell nanoparticles for environmental or energy applications.